An auto ethnographic optic: experiences of migration to multiple modes of training and participation in karate during COVID-19 - Manik, S. (From High-risk Sports to Sports as High Risk: Crisis, Captulation and Creativity during COVID-19, 2020)
Karate, a favoured and glamourized martial art in society with a rich history, was due to make its first appearance as an Olympic sport at the 2020 Tokyo mega event but this was scuppered by the arrival of the global COVID-19 pandemic. Numerous other sports were crafting innovative and flexible ways of training and participation for them to endure as a sport of choice during and after lockdown, however karate has had an intimate relationship with online platforms for some time. This chapter contributes by providing a nuanced autoethnographic optic, by a number one ranked South African master`s kata champion, into karate club training and competition participation pre and during COVID-19. Locating my argument within a theoretical framing of program risk and resilience and the notion of `arrhythmic experiences`(Thorpe 2015), underpinned by the occurrence of a natural disaster, I illuminate the multi-modal training approaches which my club and I used prior to COVID-19 due to extenuating circumstances which created an environment for bolstering resilience during the pandemic. I detail the historical reasoning and approaches to highlight my personal and club experiences over a 3-year period in migrating from a face to face dojo approach to alternative remote training blending multi modal ways of karate training to maximise participation and learning. This has significance in recognizing and navigating the efficiencies and deficiencies of multiple modes of sports training delivery for competitive and non-competitive karatekas (practitioners of karate) amidst a fluid environment demanding adaptation given the COVID-19 pandemic.